Quality Of Public Services at The Office of The East Banjarmasin Sub-District - Forasidah Forasidah (LAFADZ JAYA Publisher, 2022)
Sub-district is the division of administrative territory in Indonesia under districts or cities. The position of a sub-district is a district/city regional apparatus as a regional technical implementer which has a certain work area and is led by a sub-district head. The East Banjarmasin Sub-district Office is one of the sub-districts in the city of Banjarmasin, South Kalimantan province. This study aims to determine the implementation of the Standard Operating Procedure (SOP) and the Quality of Public Services at the East Banjarmasin District Office, Banjarmasin City. This study used the descriptive qualitative method. Data was collected by means of observation, interviews, and documentation. The results of this study indicate that the service standards at the East Banjarmasin Sub-District Office have been carried out in accordance with applicable procedures, but many people do not understand the service standards in the office, because the service standards are not installed at the East Banjarmasin Sub-District Office. The quality of public services at the East Banjarmasin Sub-district Office, Banjarmasin City can be said to be good, but there are indicators that have not been running according to community expectations, namely the unfriendliness of service employees in serving service users. So that makes people uncomfortable in taking care of all their needs.